Comparison of Connected and Disconnected Activities in the Teaching of Computational Thinking to Future Teachers - Donoso Gormaz, Gonzalo (2025)
This study addresses a crucial challenge for teacher training in Latin America: the integration of Computational Thinking into the curriculum of future mathematics teachers. Given the digital divide and limited technological resources, this study investigates whether unplugged pedagogical strategies (without the use of devices) are as effective as computer-mediated approaches in developing this essential competency. Through a pre-experimental design with 65 teaching students from a private Chilean university during the second semester of 2024, the impact on CT learning of two modalities was compared: practical workshops with digital resources versus dynamics that did not require technology. The data, collected through a validated questionnaire, revealed no significant differences in learning outcomes between the two groups. The main finding, that both methodologies are equally effective, has direct and high-impact applicability for teacher training programs in the region. It suggests that technological infrastructure barriers can be overcome through the use of non-computational activities, offering cost-effective and easy-to-implement alternatives. These conclusions validate the diversification of teaching strategies, promoting equitable access to the development of fundamental digital skills for the 21st century.